RANCANG BANGUN ALAT PELIPAT BAJU SEMI – OTOMATIS BERBASIS ARDUINO - Reni Rudiadi; Husni Sulaiman; Sri Asfirawati Halik (CV. LAJAGOE PUSTAKA, 2023)
This study aims: (1) To design an arduino-based semi-automatic clothes folder (2) To implement and test an arduino-based semi-automatic clothes folder at Cahaya Laundry. This study uses research methods (Action Research) with several stages, starting with: (1) Design, (2) Analysis, (3) Design and (4) Implementation. Based on the results of this study, it can be concluded that: (1) Design of an Arduino-based semi-automatic clothes folding device designed or manufactured using ultrasonic sensors, servos and arduino uno. The tool will work if the ultrasonic sensor detects an object, when the sensor detects the object servo 1 moves, after servo 1 moves then servo 2 moves, after servo 2 moves then servo 3 moves until the clothes are finished folding. (2) Implementation of the design of an arduino-based semi-automatic clothes folding device in a laundry room that can fold clothes semi-automatically and is able to save time in terms of folding clothes.